Psychological workplace stressors affecting secondary institution educators in Port Shepstone: A qualitative investigation - Govender, Terisha (The IIE, 2020)
According to Atwoli, Stein, Williams, Mclaughlin, Petukhova, Kessler & Koenan (2013) South Africa’s unique history gave rise to many forms of stress and illnesses that are still present amongst the population. As a result, pressure at the workplace, most specifically, the teaching environment is inevitable due to the demands within the working environment (World Health Organisation [WHO], 2020). Taking this into consideration, the research problem stemmed from the dearth of research on workplace stress factors in South Africa, specifically in community contexts such as Port Shepstone. This study sought to investigate the psychological workplace stressors affecting secondary institution educators in Port Shepstone, in terms of understanding stress in the workplace, key stressors, consequences of stress among educators, and mitigating stressors. The sample used for the study included four high school educators from Marburg, Port Shepstone. The data was collected using a semi-structured interview schedule, as it enabled the researcher to gain an in-depth understanding of the phenomenon at hand, by exploring the experiences, views, and beliefs of the participants on psychological stressors affecting them. A semi-structured interview allowed guidance and clarification if needed (Maree, 2020). In order to yield rich data, the researcher ensured that interviews were reproducible, systematic, credible, and transparent (Maree, 2020). Research conducted in Port Shepstone, South Africa, provides a more localized perspective than international literature. Findings indicated that there is a huge generational gap among teachers and learners. Hence, teachers are required to adapt to the change and diversity of children who are now present in schools. Lazarus’s transactional theory of stress and coping was relevant to this research study as it assisted the researcher understand how educators interpret stress, manage it and investigate their ability to cope with stress (Dewe, 1997). The most important contribution of this research study is to provide individuals with more knowledge in the field of stress and secondary school educators. The researcher did not have sufficient time to broaden the scope of research. As such, it is recommended that future studies may benefit from gathering a larger sample or extending the duration of the research.
Keywords: Workplace stressors; Secondary institutions of learning; Psychological effects